Analysis of Shiftability of Transmission Synchronizer based on Bench Test - Zhong Zifeng; Lu Jian (Jixie chuandong)
In order to research the shiftability of a transmission synchronizer,the synchronizer model,shifting control mechanism model and shifting robot model are built by adopting Simulation X integrated ADAMS,ABAQUS and CATIA based on shifting control and test specification of synchronous durability test bench,two kinds of shifting process conditions of 1-2 upshift and 2-1 downshift are simulated,so the shifting force,shifting displacement and input shaft speed are obtained. The simulation data are compared with test data,the analysis results show that they are basically identical,the difference is that the simulation shifting time is slightly ahead of the bench test time,the feasibility and accuracy of simulation results are verified.